Application of Ethnomathematics Through Remo Boletan Jombang Dance Culture in Elementary School Students - Lailiya, Nirmala Rahmatul; Mariana, Neni; Gunansyah, Ganes (IKIP PGRI Bojonegoro, 2025)
This research aims to apply the cultural context of the Remo Boletan dance by implementing it in class II mathematics subjects at SDN Kepuhrejo 1. Jombang. The approach used is a qualitative approach with descriptive methods. The research subjects were teachers and class II students at SDN Kepuhrejo 1 Jombang. The object of the research is the application of ethnomathematics through the culture of the Remo Boletan dance to class II students at SDN Kepuhrejo 1. The Remo Boletan dance is only implemented using existing movements, not yet linked to the subject. The data collection techniques used by researchers are questionnaires and observations, which are used to help researchers. Analysis technique to determine the interpretation of data that has been collected from previous research results. Apart from that, the data collected was then analyzed using descriptive qualitative methods, namely describing and presenting clearly and easily to understand. Thus, the mathematics subject with the Remo Boletan dance culture in class II at SDN Kepuhrejo 1 is suitable for use in learning.